Pemanfaatan Kompos Limbah Baglog Jamur Tiram (Pleurotus ostreatus) Untuk Meningkatkan Hasil Microgreen Sawi (Brassica juncea L.) - Ririn Risyaeni; Adi Maladona (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine the effect of using compost and the optimum compost dosage from baglog waste of oyster mushroom (Pleurotus ostreatus) on the yield of mustard greens (Barassica juncea L.). The method in this study used the experimental method. The research design was a single factor Complete Randomized Design (CRD) consisting of 5 trials with 4 replications to obtain 20 trials. The results of this study indicate that the application of compost from oyster mushroom baglog waste showed a significant difference in the measurement parameters of first harvest time, first day of first true leaf emergence, plant height, and planting wet weight. The most optimal dose between soil and compost as a microgreen mustard planting medium is 9.5 kg of soil + 500 grams of compost